ENGLISH GARDEN AND ITS HISTORY - M. V. Kuznetsova (Концепт: философия, религия, культура, 2019)
From ancient times people have been seeking for the beautiful and it found reﬂection in art, sculpture and literature. As the man’s life can’t be separated from nature and the desire to be surrounded by it is inherent it’s vital to visualize dear images, connected with science and technical development, new trade routes in response to the changes in the political situation in Europe, discoveries of new continents, importation and selection of new, their adaptation to the British climate Cultivation and growing plants and subsequently horticulture became an essential condition of survival on the one hand and aesthetic necessity on the other. This article traces the concept of “English garden” that has been changing for ages as well as diﬀerent styles which characterize the stages of its development and correspond to six eras of its existence. It’s worth mentioning that the 18thcentury introduced a number of styles such as Forest, Augustan, Serpentine, Picturesque and Landscape. Visiting Great Britain one can enjoy walks in the gardens of diﬀerent styles and epochs, see the traditions cared with solicitude, plunge into this or that epoch. Let us mark home researchers of this topic D.O. Shvidkovskiy and his work “ British gardens and their reﬂection in Europe”, describing British culture inﬂuence on Europe. A.P. Vergunov and V.A. Gorohov analise in detail the origin of the English garden and its appearance in Russia.